1996
DOI: 10.12968/bjon.1996.5.9.552
|View full text |Cite
|
Sign up to set email alerts
|

Accepting the challenges of pain management

Abstract: Despite advances in the treatment of pain, studies reveal that hospitalized patients continue to suffer under-recognised and unrelieved pain. Several factors contribute to this problem including health-care professionals' lack of knowledge about pain and analgesia, the inadequate use of pain assessment techniques and incomplete charting of patients' reports of pain. This article describes these challenges which must be overcome if the situation is to improve. It outlines the potential value of systematic asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Fifty percent of postoperative patients experience moderate to severe postoperative pain due to underreported and ineffective treatment of pain (Bostrom, Ramberg, Davis, & Fridlund, 1997). Ineffective postoperative pain management contributes to respiratory infections, mobility complications, and other preventable complications that increase recovery time and lead to the development of chronic pain (Bonica, 1990;Browne, 1996;Dubner, 1991). From the patient's perspective, though, the most important consequence to poor pain management is patient discomfort and suffering.…”
Section: Current Problems In Pain Management Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Fifty percent of postoperative patients experience moderate to severe postoperative pain due to underreported and ineffective treatment of pain (Bostrom, Ramberg, Davis, & Fridlund, 1997). Ineffective postoperative pain management contributes to respiratory infections, mobility complications, and other preventable complications that increase recovery time and lead to the development of chronic pain (Bonica, 1990;Browne, 1996;Dubner, 1991). From the patient's perspective, though, the most important consequence to poor pain management is patient discomfort and suffering.…”
Section: Current Problems In Pain Management Practicementioning
confidence: 99%
“…The continued incidence of severe postoperative pain indicates that recognition of the importance of pain in patients' recovery has not necessarily led nurses to improve postoperative pain management practices (Lloyd & McLauchlan, 1994;Max, 1990). Several factors contribute to poor postoperative pain outcomes, but two nursing practice issues frequently identified in the literature are deficient pain assessment and inadequate analgesia administration (Browne, 1996;Max, 1990).…”
Section: Current Problems In Pain Management Practicementioning
confidence: 99%
“…Up to three-quarters of patients experience moderate to severe pain while still in the hospital. Research has demonstrated that the intensity of postoperative pain after major surgical procedures is often underestimated and inadequately treated by health care workers (Browne, 1996). Pain is subjective in nature and there are no universally accepted means for its quantification.…”
Section: List Of Figuresmentioning
confidence: 99%
“…Physicians and nurses have often been charged with undertreating pain in their patients (Browne, 1996). One reason for this is that medical and nursing schools have traditionally overemphasized the side effects of pain medications.…”
Section: List Of Figuresmentioning
confidence: 99%
“…Pain continues to be a major concern for patients who report less than satisfactory experiences of relief and comfort while in hospital and other community settings ( Paice et al . 1991 , Closs 1994, Walker 1994, Kodiath & Kodiath 1995, Browne 1996, McMillan 1996). One possible reason for the ongoing lack of attention to human pain is the paucity of knowledge about the experience of living with pain as described by persons themselves.…”
Section: Introductionmentioning
confidence: 99%